2014
DOI: 10.2478/s11696-013-0520-8
|View full text |Cite
|
Sign up to set email alerts
|

Fouling of nanofiltration membranes used for separation of fermented glycerol solutions

Abstract: In this study, the glycerol solutions were fermented using Lactobacillus casei bacteria. The broths were pre-treated by microfiltration, followed by a further separation with nanofiltration. The latter process was carried out in two stages, using the NF270 and NF90 membranes, respectively. The concentrates thus obtained were enriched with citric acid (first stage) and then with lactic acid and glycerol (second stage). By means of SEM and AFM microscopy, as well as ATR-FTIR analysis, the intensity of membrane-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…An electrodialysis was found to be an effi cient way for salts removal and the recovery from fermentation broth 20 . The nanofi ltration (NF) is other effective process that can be used for broth desalination…”
Section: Batch Fermentationmentioning
confidence: 99%
“…An electrodialysis was found to be an effi cient way for salts removal and the recovery from fermentation broth 20 . The nanofi ltration (NF) is other effective process that can be used for broth desalination…”
Section: Batch Fermentationmentioning
confidence: 99%
“…6a. The average contact angle values of (PAH/PAA50-PSS50) 60 and (PVA/PAA50-PSS50) 60 were determined as 52 AE 1 and 45 AE 1 , respectively ( Fig. 6b and d).…”
Section: Contact Anglementioning
confidence: 99%
“…However, the retention of bacteria was not complete, and the MF permeate contained over 10 3 -10 4 cells, whereas bacteria concentration in the feed was at a level of 10 11 . These bacteria were retained when the PTFE membrane (0.2 μm, Millipore) was applied 28 . It was found that a type of membrane material and the cell-wall fl exibility triggers the transfer of the bacteria through the membranes, when the pores are smaller in size than the cell 2, 29 .…”
Section: -19mentioning
confidence: 99%
“…It was found that a type of membrane material and the cell-wall fl exibility triggers the transfer of the bacteria through the membranes, when the pores are smaller in size than the cell 2, 29 . However, a signifi cant fouling was observed due to a high hydrophobocity of PTFE 28 . A lower hydrophobocity has a polypropylene, thus the PP membranes were used in this work for MF of broth with C. freundii bacteria, which was applied for 1,3-PD syntheses from glycerol.…”
Section: -19mentioning
confidence: 99%
See 1 more Smart Citation